(2x+1)=3(x+4)

Simple and best practice solution for (2x+1)=3(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+1)=3(x+4) equation:



(2x+1)=3(x+4)
We move all terms to the left:
(2x+1)-(3(x+4))=0
We get rid of parentheses
2x-(3(x+4))+1=0
We calculate terms in parentheses: -(3(x+4)), so:
3(x+4)
We multiply parentheses
3x+12
Back to the equation:
-(3x+12)
We get rid of parentheses
2x-3x-12+1=0
We add all the numbers together, and all the variables
-1x-11=0
We move all terms containing x to the left, all other terms to the right
-x=11
x=11/-1
x=-11

See similar equations:

| -2z+(-4z)=-18 | | (2x+1)=3(x+4 | | -11a+17a-9a+16a+a=-14 | | (7/3)y=42 | | 0.2x+63=0.2x+53 | | -7u-13=-4(u-2) | | -0,5(x-4)-7,3=0,8(2-x) | | 5x+2x+3x=-70 | | 11n-5n-3n-2n=7 | | -5(1+x)+x=-3(6+2x)+6 | | 3(2x+1)=3(x+4 | | 1=v/4 | | -1|3z=8/3 | | 2x-5x=-14-7 | | 9x-58=18” | | -9a+-6a+5a+2a=16 | | 15v=8v+14 | | 20=20+z | | 9n-1n+18=n-1n+26 | | 5.3x-1.7=19.5 | | 3n-14=-7(-3n+2)+3n | | 52+r=126 | | -60=-2x-8x | | 14=v+4 | | 14w-2w-w+4w-13w=12 | | g2+2g=7 | | 2p/3-7=17 | | 5+11*2=c | | 2(5x-2)=14-8x | | -3=40x-8 | | 8(m+8)=80 | | 3x+3x+5x+5x=126 |

Equations solver categories